Significant records of plants, algae, fungi, and animals in SE Europe and adjacent regions, 4 - Curk, Aljaž (Acta biologica slovenica, 2025)
In this article, we present the first records of the bryophyte Schistostega pennata in Central Slovenia. In addition to its typical occurrence on rocky surfaces, Schistostega pennata was observed on bare loose soil. We also report a rare natural aberration of the male meadow brown butterfly, Maniola jurtina subtus-albida. This represents the first record of this aberration for the Balkan Peninsula.
Keywords: algae; alge; fungi; glive; Mahovi; Nymphalidae; plants; rastline